2018
DOI: 10.21608/ejh.2018.7518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a caffeinated energy drink and its withdrawal on the submandibular salivary gland of adult male albino rats: A histological and immunohistochemical study

Abstract: Introduction: Energy drinks provide the consumer witha combination of stimulants and energy boosters that increases the physical endurance, concentration, muscular performance and mood. Despite their benefits, many health hazards occur that may be attributed to its caffeine content. Aim: To study the effect of a caffeinated energy drink on the histological structure of submandibular salivary gland of albino rats and evaluation of the effect of its withdrawal. Materials and Methods: Thirty adult male albino rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
3
13
0
Order By: Relevance
“…These findings may suggest attempts for gland regeneration after withdrawal of the red bull energy drink. These findings were confirmed by Kassab and Tawfik [26] who observed an improvement of histological structure of submandibular gland in withdrawal group compared to RB group. CONCLUSION RB produces degenerative changes in the pancreas and causes oxidative stress.…”
Section: Energy Drinksupporting
confidence: 66%
“…These findings may suggest attempts for gland regeneration after withdrawal of the red bull energy drink. These findings were confirmed by Kassab and Tawfik [26] who observed an improvement of histological structure of submandibular gland in withdrawal group compared to RB group. CONCLUSION RB produces degenerative changes in the pancreas and causes oxidative stress.…”
Section: Energy Drinksupporting
confidence: 66%
“…Several research groups had reported various histopathological changes in different organs upon ED administration including liver, stomach, pancreas and submandibular glands but not the spleen (Khayyat et al, 2012.;Ayuob & ElBeshbeishy, 2016;Kassab & Tawfik, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Group I (Control group): included seven rats that were left untreated. Group II (Short-term Red Bull group): included seven rats which received Red Bull at a dose of 3.75 ml/kg/day orally using gastric tube for four consecutive weeks [24]. This dose (3.75 ml) contains (1.13 mg) of caffeine.…”
Section: Experimental Protocolmentioning
confidence: 99%